Reframing Sustainable Development in Emerging Economies: An Integrated Analysis of Financial Capability, Inclusive Finance, and Social Connectedness in Nepal’s Banking Ecosystem - sharma, Prabin; Bhattarai, Prakash; Aryal, Sulochana (Devkota Journal of Interdisciplinary Studies, 2026)
This study explores how financial literacy, financial inclusion, and social capital collectively shape sustainable development outcomes within the context of Nepal’s commercial banking sector. Drawing on primary data collected from 20 commercial banks, the research adopts a quantitative approach to examine the relationships among these variables using correlation and regression analysis. The findings reveal a strong and statistically significant association between financial inclusion and sustainable development, suggesting that improved access to financial services such as savings, credit, and digital bankingenhances economic participation and overall well-being. This is consistent with emerging evidence from Nepal, where financial inclusion initiatives have contributed to income generation and reduced financial vulnerability among underserved populations.The analysis further demonstrates that financial literacy exerts the most substantial influence on sustainable development, indicating that individuals’ ability to understand and manage financial resources plays a decisive role in shaping long-term economic and social outcomes. In the Nepalese setting, where disparities in financial knowledge remain evident across regions and demographic groups, this finding highlights the importance of strengthening financial education as a core development strategy. Social capital, although showing a comparatively smaller direct effect, is found to be positively associated with sustainable development, reflecting the supportive role of trust, networks, and community engagement in facilitating access to financial opportunities.The regression findings demonstrate that financial access, financial capability, and social cohesion collectively contribute to sustainable development in Nepal. The model indicates that these factors are not independent drivers; instead, their combined influence plays a meaningful role in shaping long-term developmental outcomes. The results further imply that isolated policy measures are unlikely to generate substantial progress unless they are supported through integrated and inclusive strategies. Strengthening financial inclusion alongside improving financial literacy and community-level cooperation can create a more balanced and sustainable development framework. These findings offer practical implications for policymakers, development agencies, and financial institutions in formulating contextually relevant initiatives that support Nepal’s broader sustainable development agenda and the achievement of the Sustainable Development Goals (SDGs)